Psychomotor Retardation in Elderly Untreated Depressed Patients - Beheydt, Lieve Lia; Schrijvers, Didier; Docx, Lise; Bouckaert, Filip; Hulstijn, Wouter; Sabbe, Bernard (Frontiers in Psychiatry, 2015)
Background: Psychomotor retardation (PR) is one of the core features in depression according to DSM V (1), but also aging in itself causes cognitive and psychomotor slowing. This is the first study investigating PR in relation to cognitive functioning and to the concomitant effect of depression and aging in a geriatric population ruling out contending effects of psychotropic medication. Methods: A group of 28 non-demented depressed elderly is compared to a matched control group of 20 healthy elderly. All participants underwent a test battery containing clinical depression measures, cognitive measures of processing speed, executive function and memory, clinical ratings of PR, and objective computerized fine motor skill-tests. Statistical analysis consisted of a General Linear Method multivariate analysis of variance to compare the clinical, cognitive, and psychomotor outcomes of the two groups. Results: Patients performed worse on all clinical, cognitive, and PR measures. Both groups showed an effect of cognitive load on fine motor function but the influence was significantly larger for patients than for healthy elderly except for the initiation time. Limitations: Due to the restrictive inclusion criteria, only a relatively limited sample size could be obtained. Conclusion: With a medication free sample, an additive effect of depression and aging on cognition and PR in geriatric patients was found. As this effect was independent of demand of effort (by varying the cognitive load), it was apparently not a motivational slowing effect of depression.